The Relationship between Gadgets Use and Sleep Quality of Medical Education Students at the Faculty of Medicine, Syiah Kuala University in 2023 - muhammad lana ovanda; Tilaili Ibrahim; Sakdiah; Muhammad Yani; Rovy Pratama (SCRIPTA SCORE Scientific Medical Journal, 2025)
Background:The use of gadgets has a big impact in making everyday communication easier. Sleep quality is a measure of how easy it is for a person to start sleeping and maintain sleep. The quality of a person's sleep can be described by the length of time they sleep and complaints or after waking up. Objectives:This study aims to determine the relationship between the use of devices and sleep quality among medical students class of 2021, Faculty of Medicine, Syiah Kuala University. Methods: This research uses quantitative methods with a cross sectional approach. The sampling technique used is cluster sampling. The analysis techniques used are univariate tests and bivariate tests. The data used is primary data and secondary data. The number of samples in this study was 199 respondents. Results:The results of the research show that 11.6% of medical students at the class of 2021 medical school at Syiah Kuala University are in the normal category and 88.4% are not normal. Meanwhile, 53.8% of the sleep quality was in the good category and 46.2% was poor. Conclusion:This research shows that there is a relationship between the use of devices on sleep quality and value (p= 0.002).Latar Belakang: Penggunaan gawai memiliki dampak besar dalam mempermudah komunikasi sehari-hari. Kualitas tidur adalah ukuran dimana seseorang itu dapat kemudahan dalam memulai tidur dan untuk mempertahankan tidur, kualitas tidur seseorang dapat digambarkan dengan lama waktu tidur dan keluhan-keluhan ataupun sehabis bangun tidur. Objektif: Penelitian ini bertujuan mengetahui gambaran hubungan antara penggunaan gawai terhadap kualitas tidur pada mahasiswa pendidikan dokter angkatan 2021 fakultas kedokteran universitas syiah kuala. Metode: Penelitian ini menggunakan metode kuantitatif dengan pendekatan cross sectional. Teknik pengambilan sampel yang digunakan adalah cluster sampling. Teknik analisis yang digunakan yaitu uji univariat dan uji bivariat. Untuk data yang digunakan adalah data primer dan data sekunder. Jumlah sampel pada penelitian ini sebanyak 199 responden. Hasil: Hasil penelitian menunjukkan penggunaan gawai pada mahasiswa Pendidikan dokter Angkatan 2021 fakultas kedokteran Universitas Syiah Kuala sebanyak 11,6% termasuk kategori normal dan 88,4% tidak normal. Sedangkan kualitas tidurnya sebanyak 53,8% termasuk kategori baik dan 46,2% kurang baik. Kesimpulan: Pada penelitian ini menunjukkan adanya hubungan antara penggunaan gawai terhadap kualitas tidur dengan nilai (p = 0,002).